The Urinary Liver-Type Fatty Acid Binding Protein (L-FABP) in Early Detection and Outcome Prediction of Sepsis-Associated Acute Kidney Injury - Ghi Nguyen Hai; Binh Nguyen Gia; Hoa Do Thanh; Cuong Nguyen Thai; Duc Vu Anh; Anh Duong Duc; Duong Le Xuan Xuan (Archives of Academic Emergency Medicine)
Introduction: Acute kidney injury (AKI) is one of the most frequent complications in septic shock cases, and has a high mortality rate. The aim of this study was to determine the value of urinary liver-type fatty acid binding protein (L-FABP) in early detection and outcome prediction of AKI in patients with sepsis and septic shock.